The Double Inflammatory Burden: Red Cell Distribution Width as an Exploratory Biomarker for Functional Outcome in Ischemic Stroke with Comorbid Systemic Lupus Erythematosus - Resita Indah Sukraputri; Endang Kustiowati; Hexanto Muhartomo; Dodik Tugasworo; Aris Catur Bintoro; Elta Diah Pasmanasari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Ischemic stroke in patients with systemic lupus erythematosus (SLE) presents a highly unique clinical phenotype characterized by amplified systemic inflammation, profound endothelial dysfunction, and a pervasive prothrombotic state. The combined, synergistic effect of this double inflammatory burden exacerbates acute neuronal injury and leads to significantly poorer clinical recovery. This study evaluated Red Cell Distribution Width (RDW), a widely available surrogate marker of systemic inflammation, oxidative stress, and impaired erythrocyte deformability, as a prognostic biomarker for functional outcomes in this specific, high-risk inflammatory phenotype. Methods: In this retrospective analytical pilot study, 34 adult patients diagnosed with acute ischemic stroke and comorbid SLE were analyzed. Admission RDW values, National Institutes of Health Stroke Scale (NIHSS) scores, and 90-day Modified Rankin Scale (mRS) scores were collected. A poor functional outcome was rigorously defined as an mRS score of 3–6. Statistical evaluation included Mann-Whitney U tests, Spearman rank correlation, receiver operating characteristic (ROC) curve analysis, and multivariable logistic regression to adjust for baseline neurological severity. Results: RDW demonstrated a statistically significant positive correlation with initial stroke severity (NIHSS; r = 0.397; p = 0.020) and 90-day functional disability (mRS; r = 0.711; p < 0.001). The median RDW was significantly higher in patients with poor outcomes compared to those with good outcomes (15.6% versus 13.4%, p < 0.001). ROC analysis yielded an excellent Area Under the Curve of 0.89 (p < 0.001) with an optimal predictive cut-off established at 13.75%. In multivariable analysis adjusting for baseline stroke severity, an admission RDW of 13.75% or higher remained a strongly associated factor for severe long-term disability (adjusted Odds Ratio: 14.82, 95% Confidence Interval: 1.95–112.45, p = 0.009). Conclusion: RDW is a promising, inexpensive, and universally available prognostic biomarker that demonstrates a strong association with severe functional disability in ischemic stroke patients with comorbid SLE, accurately reflecting the profound neurotoxic impact of the double inflammatory burden.